Technological surveillance in byproducts from the fish agroindustry [Vigilancia tecnológica en subproductos de la piscicultura] (2017)
In the article, we present topics of competitiveness, value chain and strategic initiatives of the Colombian fishing sector, complemented with a Technological Surveillance exercise in three topics related to fish byproducts: hydrolyzed protein, formulation of concentrated foods and probiotics. The methodology used consisted of querying search equations in scientific databases such as Scopus and databases for patents such as WIPO and Free Patents on-Line, as well as identifying critical surveillance factors and subsequent selection of studies that support technological strengthening for each selected theme. Amongst the main results are the use of technologies aimed at the development of products with a high degree of added value, combining topics leading the research worldwide, such as functional foods, edible drugs, nutritional compositions, food supplements, all oriented towards areas of study of agricultural and biological sciences. © 2017.